Non genetic factors affecting udder type traits in Sahiwal cattle - Togla, oshin; Deb, SM; Sagar Kadyan; PB Nandhini; Sushil Kumar (Indian Journal of Dairy Science, 2022)
Non genetic factors affecting udder type traits in Sahiwal cattle Abstract: The present study was planned to find out the magnitude of environmental factors affecting udder type traits in Sahiwal cattle. Fourteen type of udder traits were measured for each of randomly selected 100 lactating cattle maintained at Livestock Research farm, NDRI, Karnal, India. The data were analysed by least squares methods using the general linear model procedures including parity, stage of lactation and season of calving at classification as fixed effects. Traits viz. Udder balance, Rear Udder Height, Teat Diameter, Teat Length, Central Ligament, Udder Circumference, Udder Width and Teat Circumference were significantly (p<0.05) affected by parity. Stage of lactation was significant (P<0.05) source of variation for Shortest distance from teat ends to floor, Rear Udder Height, Central ligament and Udder Circumference while season of calving significantly (p<0.05) affected Rear Udder Height, Teat Length and Rear Udder Width. It is, therefore, suggested that in breeding value estimation for udder conformation, these environmental factors should be considered which would justify focusing genetic improvement in Sahiwal cattle.